(untitled) (Asian Journal of Current Engineering and Maths, 2013)
All GSM operators use Key Performance Indicators (KPIs) to judge their network performance and evaluate the Quality of Service (QoS) regarding end user perceived quality. KPIs are becoming increasingly important in the context of network rollouts as well as within mature network optimization cycles. The performance of the mobile network is measured based on several counters describing the most important events over a measurement period. The KPIs are derived with the help of these counters. All the KPIs listed in this reportare very important and are used by all mobile operators.The study made a comparative analysis of certainKPIsto NCA Standards to assess the network performance of Airtel on KNUST Campus. Results obtained from graphical representations showed which Cell Sites proved good according to the NCA Standards and which ones didn’t with respect to the individual KPIs. It was concluded that the network performed generally well but had a few minor problems with two cells sites which can be looked at and optimized.